Humanitarian Diplomacy in Action: Examining Muhammadiyah as a Model for Faith-Based Organizational Engagement - Husein, Rahmawati; Kurniawan, Bachtiar Dwi; Kurniawati, Nawang (Universitas Muhammadiyah Yogyakarta, 2024)
The intersection of faith organization and international humanitarian efforts remains a relatively underexplored domain within the broader discourse of non-governmental organizational studies. This research delves into the operational dynamics of Muhammadiyah, a prominent Indonesian Faith-Based Organization (FBO), as it engages in global humanitarian endeavors—a practice herein referred to as ‘humanitarian diplomacy’. The primary objective of this study is to elucidate the contributions of Muhammadiyah in humanitarian diplomacy, thereby filling a gap in the literature that predominantly focuses on International Non-Governmental Organizations (INGOs) and state actors, with scant attention to national or FBO. This study parses the organization’s activities into four core dimensions, as stated by Minear and Smith (2007): the orchestration of presence, the negotiation of access, the mobilization of advocacy, and the oversight of programmatic assistance. A narrative of Muhammadiyah’s operational strategies and diplomatic engagements was reconstructed through a qualitative methodological approach, including interviews with Muhammadiyah affiliates and a comprehensive review of secondary data sources such as academic theses, research articles, and news reports. The findings revealed that Muhammadiyah’s humanitarian work has been closely aligned with the theoretical tenets proposed by Minear and Smith. The organization’s effective arrangement of its presence in various regions, strategic negotiation for access in complex environments, active engagement in advocacy to amplify the needs and rights of affected populations, and diligent monitoring of assistance programs have collectively demonstrated a sophisticated model of humanitarian diplomacy at work. This study not only contributes to a more nuanced understanding of FBOs in humanitarian diplomacy but also provides a template for other national and local NGOs seeking to navigate the challenges of international humanitarian work.